The Juridical Study of the Implementation of Hotel Condominium Agreements - Arifin, Himawan (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
Hotel condominiums are accommodations that can be used as an alternative to support the high mobility of today's society. This has made Condotel grow rapidly in Indonesia, however, this development is not in line with the existence of clear legal regulations. The approach method used in this qualitative legal research is a sociological juridical approach, which is an approach by seeking information through direct interviews with informants empirically first and then followed by conducting research on secondary data found in literature studies through theoretical steps. Based on the research conducted, it can be seen that the implementation of hotel condominium agreements so far has not had a legal footing in Indonesia, this has resulted in many developers and builders often seeking large profits without heeding the principles of good ethics in buying and selling agreements and managing hotel condominiums. The weaknesses that make the condo hotel agreement policy in Indonesia not fair are the weaknesses in the laws and regulations in the form of non-regulation of the contents of the condo hotel agreement and the position of the condo hotel in Act No. 20 of 2011, the weakness in law enforcement in the form of the lack of oversight regarding the sale agreement purchase and management of hotel condos, and the habit factor of hotel condominium development and construction actors who mostly seek profit through sale and purchase agreements and management of hotel condominiums by setting aside consumers or hotel condo owners. The solution that can be done is to make legal regulations specifically related to hotel condos, considering that hotel condos are different from condos in general.Keywords: Agreement; Condominium; Hotel; Juridical.